2019
DOI: 10.3390/polym11121951
|View full text |Cite
|
Sign up to set email alerts
|

Caseinate-Stabilized Emulsions of Black Cumin and Tamanu Oils: Preparation, Characterization and Antibacterial Activity

Abstract: Caseinate-stabilized emulsions of black cumin (Nigella sativa) and tamanu (Calophyllum inophyllum) oils were studied in terms of preparation, characterization, and antibacterial properties. The oils were described while using their basic characteristics, including fatty acid composition and scavenging activity. The oil-in-water (o/w) emulsions containing the studied oils were formulated, and the influence of protein stabilizer (sodium caseinate (CAS), 1–12 wt%), oil contents (5–30 wt%), and emulsification meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…The destabilization of the emulsion was a direct result of the oil content since the amount of the emulsifier added was constant. Referring to the studies conducted for emulsions with tamanu oil and casein, it can be concluded that the use of a larger amount of stabilizing agent with an increase in oil concentration has a beneficial effect on the obtained creaming index value [ 15 ]. Due to the emulsifier used, lecithin showed better stabilizing properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The destabilization of the emulsion was a direct result of the oil content since the amount of the emulsifier added was constant. Referring to the studies conducted for emulsions with tamanu oil and casein, it can be concluded that the use of a larger amount of stabilizing agent with an increase in oil concentration has a beneficial effect on the obtained creaming index value [ 15 ]. Due to the emulsifier used, lecithin showed better stabilizing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies on emulsions with tamanu oil indicate its poor emulsifying properties. It has been shown that oils with high viscosity tend to form emulsions with a larger particle size [ 15 ]. The most viscous of the oils applied is tamanu oil, which is roughly four times more viscous than inca inchi oil [ 3 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tamanu oil emulsions (Figure 3c,d), a slight thermal shift in the range of 0.06-2.2 • C between the melting and solidification curves occurred. Urbánková et al [45] studied tamanu and black cumin oil emulsions with the addition of sodium caseinate, and observed an average emulsion size in the range from 0.3 to 1.5 µm. In the current study, the average emulsion size of tamanu oil with Tween 20 (Figure 6) and Tween 80 (Figure 7) was 5-16 and 8-17 µm, respectively.…”
Section: Thermophysical Characterization Of Pcm Emulsionsmentioning
confidence: 99%
“…The oils and selected emulsions were proven to act against Gram-positive strains, mainly against Staphylococcus aureus and Bacillus cereus. Regrettably, Gram-negative species were fully resistant to their action [30].…”
mentioning
confidence: 99%